2001
DOI: 10.1021/ma010552h
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics in Microphase-Separated Poly(ethylene oxide)-block-poly(1,4-butadiene)

Abstract: We studied the crystallization kinetics in a diblock copolymer system exhibiting different mesophase structures in the melt. A symmetric poly(ethylene oxide)-block-poly(1,4-butadiene) (PEO-b-PB) was blended with a low molecular weight PB homopolymer to yield the block copolymer blends containing lamellar, cylindrical, and spherical PEO microdomains. The crystallization kinetics of PEO blocks in these nanoscaled microdomains was then studied by monitoring the development of crystallinity in the course of isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
220
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(230 citation statements)
references
References 28 publications
10
220
0
Order By: Relevance
“…For our PB-PEO/PB films, T g of the PB matrix is well below the crystallization temperatures (T c 's), which means that the PB matrix is in the rubbery state for the temperature range accessed. However, as Chen et al 10 demonstrated, this diblock is strongly segregated, with confinement further strengthened by the presence of the PB homopolymer. Thus, crystallization is effectively confined within the spherical domains without breakout or domain coalescence occurring when T c 's are reached.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…For our PB-PEO/PB films, T g of the PB matrix is well below the crystallization temperatures (T c 's), which means that the PB matrix is in the rubbery state for the temperature range accessed. However, as Chen et al 10 demonstrated, this diblock is strongly segregated, with confinement further strengthened by the presence of the PB homopolymer. Thus, crystallization is effectively confined within the spherical domains without breakout or domain coalescence occurring when T c 's are reached.…”
Section: Resultsmentioning
confidence: 94%
“…8,10 The transition occurs over a 5 8C range, which is expected because each domain must create its own nucleus, and this is a process that has been shown to occur stochastically. 8,28 In agreement with the findings of Röttele et al, 15 we also have observed a wide temperature range (%5 8C) over which melting occurs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations